PRINSIP SYARIAH DALAM MANAJEMEN RUMAH SAKIT - Mustaghfirin, Muhammad; Ziyadatin Ilmi, Anugrahi Putri; Ratih, Dewi; Latifah, Eny (JISEF : Journal Of International Sharia Economics And Financial, 2023)
This article examines sharia principles in sharia hospital management, covering the basic concepts of sharia management, leadership in sharia hospital management, service quality and ethics, human resource management (SDA), and hospital financial management. This research uses descriptive qualitative methods through a library research approach. The basic concept of sharia management is explained as the application of Islamic values ??in every aspect of hospital management. Effective and ethical leadership based on sharia principles is identified as a key factor in achieving organizational success. This article also highlights the importance of service quality and ethics according to Islamic teachings to provide optimal services to patients. Apart from that, efficient and transparent natural resource management and financial management in accordance with sharia principles is an important focus. The included case studies illustrate the implementation of these principles in real practice, as well as the challenges and solutions encountered.